Feasibility of Exempting Foster Father from the Penalty of Theft in the Light of Islamic Jurisprudence - Sayyed Amirali Sadeghi Moghaddam; hamid rustaei sadrabadi; Abbas Kalantari Khalilabad; mohammad mahdi barghi (فقه و حقوق خانواده)
a Foster kinship is established through the breastfeeding of the child, as stipulated in Article 1046 of the Civil Code, when a child is breastfed by a woman who is not the child's biological Mother. This kinship prohibits marriage between foster relatives and does not entail the legal consequences of a blood relationship such as inheritance or maintenance. Following the Islamic Penal Code and according to Shiite jurisprudence, theft is punished by amputation. Although kinships are generally not exempt from this punishment, Article 268 of the Islamic Penal Code exempts a father from the Hadd punishment for stealing from his child. The use of the general word of "father" in both legal and jurisprudential texts raises the fundamental question that if the of whether a foster father, who shares a milk kinship with the child, would also be exempt from the punishment of hand amputation if he steals from the property of his foster child and would be committed in all circumstances? This descriptive-analytical study based on the library research examines the reasons behind this exemption and compares them with the other jurisprudential and legal rules concluded that the legislator tends to interpret the rule of dirā' in a broad manner by establishing Articles 120 and 121 of the Islamic Penal Code and with referring to the hadith "And you are the owner of the property," which refers to the obligation to respect the father, includes kinship resulting from breastfeeding which refers to the obligation to respect the father, also includes kinship resulting from breastfeeding. The studies show that a foster father, like a biological father, is also entitled to respect and is exempt from the punishment of Hand amputation for stealing from his foster child. The Quranic verse on theft is not absolute, and Islamic traditions also emphasize the obligation of respecting one's father, regardless of whether the relationship is biological or foster.